2006
DOI: 10.1186/1471-2407-6-194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of young age at presentation on survival in breast cancer

Abstract: Background: Young age remains a controversial issue as a prognostic factor in breast cancer. Debate includes patients from different parts of the world. Almost 50% of patients with breast cancer seen at the American University of Beirut Medical Center (AUBMC) are below age 50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
160
3
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 18 publications
17
160
3
11
Order By: Relevance
“…The difference between the mean age at diagnosis of triplenegative breast cancer was not significant between our study and international studies (52 years versus 50 years), whereas the mean age at diagnosis of breast cancer, independent of phenotype, was 52 years in Lebanon versus 63 years in the U.S. [11][12][13].…”
Section: Discussionmentioning
confidence: 84%
“…The difference between the mean age at diagnosis of triplenegative breast cancer was not significant between our study and international studies (52 years versus 50 years), whereas the mean age at diagnosis of breast cancer, independent of phenotype, was 52 years in Lebanon versus 63 years in the U.S. [11][12][13].…”
Section: Discussionmentioning
confidence: 84%
“…It has become evident that young women with breast cancer have a poorer prognosis than older women; their frequency of recurrence is higher [1,2], and their survival lower [1,[3][4][5][6]. In a recent Danish study of low-risk breast cancer patients enrolled in the Danish Breast Cancer Group (DBCG) 89a-protocol [7], we found that local recurrence was associated with distant metastasis (DM) among younger patients ( 45 years).…”
mentioning
confidence: 99%
“…Reviewed the available American data (SEER database), it was found that the mastectomy rate was the highest (58.2%) [16]. Other research also pointed around half of the elder cases (53.1%) above 50 years treated by chemotherapy in compare to younger group (76.5%) [38]. The current study supported that cases of BC treated with a multidisciplinary approach, merging the efforts of surgery, chemotherapy, and radiation therapy based on the BC stages [37].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistence with outdated risk factors for developing BC, which are null parity, early menarche, late pregnancy and menopause, increase intake of diet rich in fat [21]. It was been testified in another study that the incidence of comorbidity disease was 15.4% hypertension, 7.1% diabetes, 34% smoking and the elder BC cases had diabetes, hypertension, and cardiac diseases (P<0.001) [38].…”
Section: Discussionmentioning
confidence: 99%